2019
DOI: 10.1016/j.radonc.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

MRI visibility of gold fiducial markers for image-guided radiotherapy of rectal cancer

Abstract: R.P.J. van den Ende). Radiotherapy and Oncology 132 (2019) 93-99

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Positioning of prostate cancer patients using fiducial markers has been subject to a relatively large number of studies. These markers are visible on MR, but not with 100% sensitivity or specificity [13], [26], [27], [28], [29]. There is therefore an obvious need for patient specific quality control measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positioning of prostate cancer patients using fiducial markers has been subject to a relatively large number of studies. These markers are visible on MR, but not with 100% sensitivity or specificity [13], [26], [27], [28], [29]. There is therefore an obvious need for patient specific quality control measures.…”
Section: Resultsmentioning
confidence: 99%
“…the use of S-CT for positioning of prostate cancer patients with fiducial markers is a scenario which highlighted in literature. The markers are not directly visualized with MR, but appear as a signal void, which may be confused with for example calcifications [13], [26], [27], [28], [29]. The challenges connected to MR-only treatment planning have been described in a recent review [18].…”
Section: Introductionmentioning
confidence: 99%
“…The generalizability of this algorithm for MRI-only radiotherapy simulation of other anatomical sites such as the rectum and pancreas may also be worth investigating. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we evaluated the MRI visibility of the fiducials, and we identified 17 out of 34 fiducials on the first MRI and 9 out of 30 fiducials on the second MRI. 27 The Visicoil 0.75 and the Gold Anchor were the best visible fiducials on MRI. In addition, a consensus meeting with a radiologist (EP) and a resident radiation oncologist (ER) was held to identify more fiducials for this study.…”
Section: Mri Processingmentioning
confidence: 93%